Synthesis and Chemical Structure Elucidation of Two Schiff Base Ligands, Their Iron(II) and Zinc(II) Complexes, and Antiradical, Antimicrobial, Antioxidant Properties - Turan, Nevin; Savci, Ahmet; Buldurun, Kenan; Alan, Yusuf; Adigüzel, Ragıp (Letters in Organic Chemistry, 2016)
Background: Fe(II) and Zn(II) complex series have been synthesized from Schiff base ligands derived from furan-2-carbaldehyde and thiophene-2-carbaldehyde. Elemental, infrared, ultraviolet- visible, NMR and thermal analysis, also mass spectroscopy and magnetic susceptibility measurements were performed to explain the structures of these synthesized ligands and their metal complexes. The formulas based on analytical, spectral, and magnetic studies, the complexes can be demonstrated as [M(L1)2](H2O)n, [M(L2)2](H2O)n, where M = Zn(II) and Fe(II). An octahedral geometry was suggested for the Zn(II) and Fe(II) complexes. The antioxidant, antiradical and antimicrobial properties of the Zn(II) and Fe(II) complexes were investigated using different in vitro assays. Some of the complexes showed reasonable amount of antioxidant and antimicrobial activity.
Keywords: Antimicrobials